PEMANFAATAN EDIBLE FILM BERBAHAN PATI SINGKONG ALTERNATIF KEMASAN BIOPOLIMER UNTUK KEBERLANJUTAN PANGAN - EVRILIYANI, NINA; AMANDA, SALMA TRISYA; ALIANO, KEIYSHA BERLIANINDITA; PRATAMA, GRESHAM PANGIHUTAN; MAULANI, SYIFA FAJAR; DARMAWAN, RAIHAN MAULANA (Ganec Swara, 2025)
Synthetic plastic takes a long time to decompose and contributes to environmental pollution. Edible films made from cassava starch have the potential to be an eco-friendly solution as biodegradable food packaging. This study aims to evaluate the characteristics of edible films with the addition of glycerol and sorbitol as plasticizers. The research methods included literature review and experiments by combining various weights of cassava starch with volumes of glycerol and sorbitol. Physical characteristics such as thickness, tensile strength, and elongation were tested. The results showed that edible films with sorbitol had an average tensile strength of 1135.57 cN and elongation of 24.88%, which were superior to those with glycerol, which had an average tensile strength of 980.67 cN and elongation of 21.5%. Edible films with sorbitol have great potential as an environmentally friendly alternative for food packaging.